Study on the Utilization and Implementation of Urban Residual Space Renewal under the Perspective of Inventory Renewal: Taking Suzhou Main City as an Example - Yuan, Xiaonian (International Journal of Natural Resources and Environmental Studies, 2025)
Under the contradiction between residents' growing demand for diversified public space and the increasing tension of available space in urban built-up areas, revitalization of surplus space has become a new trend. With land within the urban cbuilt-up areas, there is a lack of street-level public space or even lower-level small and micro-public space in the land use arrangement, therefore, starting from the low-efficiency or surplus space and transforming it into a new functional space that meets citizens' needs has become an An important way to cope with the imbalance in the distribution of public space and the diversification of residents' spatial needs. However, there is a lack of clear and systematic discussion on residual space in domestic research. Firstly, it clarifies the definition and characteristics of residual space, secondly, this paper studies the problems and reasons for the formation of some residual space, clarifies the value of residual space, discusses its subdivision and puts forward improvement opinions, and puts forward the implementation of co-creating mode, implementation and management paths, and safeguards for residual space.